2004
DOI: 10.1111/j.1365-2141.2004.05303.x
|View full text |Cite
|
Sign up to set email alerts
|

High‐dose idarubicin and busulphan as conditioning to autologous stem cell transplantation in adult patients with acute myeloid leukaemia

Abstract: Summary Between 30 and 50% of patients with acute myeloid leukaemia (AML) relapse after autologous stem cell transplantation (ASCT). One possibility of reducing the relapse rate could be the adoption of conditioning regimens specifically designed for AML. We report treatment results achieved with a new conditioning for ASCT, based on high‐dose idarubicin (IDA) plus oral busulphan. Patients (n = 40) were conditioned with a regimen consisting of 3 d continuous intravenous infusion IDA at 20 mg/m2, followed by 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…35 The association of idarubicin with busulfan for autologous SCT in AML patients caused profound mucosal derangement in 82% of patients. 36 High doses of melphalan (200 mg/m 2 ), given prior to autologous SCT for multiple myeloma, caused mucosal injury in about 35% of them; 37 intermediate doses (100 mg/m 2 ) significantly reduced the incidence of mucositis to 23%, as reported in a study including patients over 70 years old. 38 In the allogeneic SCT setting, the incidence of mucositis reaches 75 to 100%, depending on the type of disease and procedure and on the conditioning regimen;…”
Section: Mucositis During Transplantationmentioning
confidence: 61%
“…35 The association of idarubicin with busulfan for autologous SCT in AML patients caused profound mucosal derangement in 82% of patients. 36 High doses of melphalan (200 mg/m 2 ), given prior to autologous SCT for multiple myeloma, caused mucosal injury in about 35% of them; 37 intermediate doses (100 mg/m 2 ) significantly reduced the incidence of mucositis to 23%, as reported in a study including patients over 70 years old. 38 In the allogeneic SCT setting, the incidence of mucositis reaches 75 to 100%, depending on the type of disease and procedure and on the conditioning regimen;…”
Section: Mucositis During Transplantationmentioning
confidence: 61%
“…Some pilot studies suggest that addition of IDA to the standard conditioning regimens may improve OS and DFS of patients with AML treated with ABMT. [36][37][38] On the basis of these data, we conducted a retrospective trial comparing IDA intensified BUCY2 conditioning regimen with standard BUCY2 regimen in allo-SCT. Consistent with the results of the pilot study, the 2-year OS and DFS rates herein observed for patients undergoing transplantation for high-risk leukemia using the IDA-BUCY2 regimen were better than those using the BUCY2 regimen.…”
Section: Discussionmentioning
confidence: 99%
“…BU and continuous infusion IDA as a conditioning regimen for auto-SCT in patients with AML and a better outcome was found. [16][17][18][19] Therefore, we investigated combinations of BU with IDA instead of BUCY2 as a myeloablative conditioning regimen that may result in effective and well-tolerated myeloablative conditioning regimens. Here, we report the results obtained in our institute retrospectively by comparing standard vs IDA-intensified BUCY2 (IDA-BUCY2) myeloablative conditioning regimens in allo-PBSCT for high-risk hematological malignancies over a period of several years.…”
Section: Introductionmentioning
confidence: 99%
“…23 The association of idarubicin with BU for autologous HSCT in patients with AML caused profound mucosal derangement and pain in 82% of patients. 24 In myeloma patients, a high dose (200 mg/m 2 ) of melphalan is associated with a 30-35% incidence of OM. 25 Conversely, the reported incidence of severe OM associated with intermediate doses of melphalan (100 mg/m 2 ) in myeloma patients is under 10%.…”
Section: Epidemiology and Causal Factors Of Specific Pain Syndromes Imentioning
confidence: 99%